South–south mobility: economic and health vulnerabilities of Bangladeshi and Nepalese migrants to India. Issue 2 (3rd August 2016) - Ray Saraswati, Lopamudra; Sarna, Avina; Rob, Ubaidur; Puri, Mahesh; Singh, Roopal Jyoti; Sharma, Vartika; Kundu, Amitabh
ABSTRACT: This paper reports the results of a three-country study of the social, economic and health vulnerabilities of migrants from Bangladesh and Nepal living in India and of returnees. Overall, migration was found to be economically beneficial for those who succeed in the host labour market. However, it is associated with significant psychosocial and health vulnerabilities for most migrants in both communities. Further, migrants returning to their home countries with expectations of a better life continue to be in debt and experience poor health, indicating that migration may not always alleviate economic distress and highlighting the need for financial guidance.